Dopaminergic co-transmission with sonic hedgehog inhibits abnormal involuntary movements in models of Parkinson’s disease and L-Dopa induced dyskinesia - Lauren Malave (Nature Portfolio, 2021)
Lauren Malave et al. examine the impact of sonic hedgehog signaling in the dorsal striatum in L-Dopa induced dyskinesia (LID) animal models. Their results suggest that increasing sonic hedgehog signaling can reduce the severity of LID and abnormal involuntary movements, suggesting future therapeutic approaches to mitigate dyskinetic comorbidities of long-term treatment with L-Dopa.